Resin composition for degradable and recyclable low-loss white copper-clad plate as well as preparation, application and recycling method of resin composition
By developing a degradable curing agent with a specific structural formula and a resin composition combining a variety of resin components, the problems of difficulty in degrading white copper clad plates and large dielectric loss are solved, and efficient degradation and recycling are achieved, suitable for high-frequency and high-speed coating. Copper plate field.
Patent Information
- Application Number
- CN202510074161.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2045-01-17
AI Technical Summary
The existing white copper clad plate has difficulty in degrading and large dielectric loss, which cannot meet the needs of high-frequency and high-speed applications.
Develop a resin composition for low loss white copper clad plate that can be degraded and recovered, including a degradable curing agent with a specific structural formula, combined with components such as alicyclic epoxy resin, polyphenylene ether resin, hydrocarbon resin, etc., to prepare semi-cured sheets and coatings Copper plates and provide recycling methods.
It has achieved efficient degradation and recycling of white copper clad plates, reduced degradation time by more than half, significantly improved flame retardant performance, excellent dielectric performance, and is suitable for high-frequency and high-speed copper clad plate fields.
Smart Images

Figure SMS_1 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of copper-clad laminates, and in particular relates to a degradable and recyclable low-loss resin composition for white copper-clad laminates and a preparation, application and recycling method thereof. Background Art
[0002] Traditional PCB boards often use thermosetting resin materials, which are the most difficult to handle and recycle because they are insoluble and infusible. At present, the main methods for recycling PCBs include landfill, mechanical and chemical methods. The landfill and mechanical methods have low separation efficiency; chemical methods include heat treatment, solvent, supercritical liquid, etc., which generally require high temperature and high pressure conditions or highly corrosive liquids, high energy consumption, high risk factor, and easy to cause secondary pollution. In the context of the increasingly severe environmental situation, the treatment and recycling of PCB waste requires green and environmentally friendly methods with high separation efficiency, high recycling value, appropriate cost and suitable for industrialization, which requires the PCB board itself to have a degradable function.
[0003] The Chinese patent (CN 106750182 A) discloses that a non-degradable curing agent is added to a degradable curing agent system to jointly cure epoxy, and the prepared laminates and printed circuit boards are recyclable and degradable, but the process of the degradable curing agent used is complicated, and the dielectric loss of the board (1GHz) is as high as 0.016. It can be seen that its dielectric loss is even greater at 10GHz, which cannot meet the application requirements of high-frequency and high-speed copper-clad laminates. There is also a technology for preparing degradable resin materials using curing agents containing disulfide bonds, but the degradation efficiency is still at a low level.
[0004] At present, alicyclic epoxy resin is the mainstream resin system for white copper clad laminates and PCB boards used to encapsulate light-emitting diodes (LEDs). However, the laminated boards of this system have high heat resistance and excellent acid and alkali corrosion resistance. It is more difficult to recycle such waste boards and the degradation conditions are more stringent. However, none of the curing agent application technologies mentioned above have been applied to alicyclic epoxy resins. With the high frequency and high speed of 5G signal transmission and the high integration of electronic products, the copper clad laminate industry is developing rapidly. For white resin compositions with low dielectric loss and copper clad laminates, it is urgent to develop a curing agent that is easier to degrade and recycle and can be applied to alicyclic epoxy resins to meet higher terminal application requirements. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: The present invention provides a degradable and recyclable low-loss white copper-clad laminate resin composition, comprising a degradable curing agent; the degradable curing agent comprises one or more degradable curing agents having the following structural formula: Wherein, R1 includes hydrogen atom, alkyl, cycloalkyl, heterocyclic group, heterocyclic alkyl, alkenyl, cycloalkenyl, alkynyl, aromatic group, heteroaromatic group, alkylene oxide group, alkylene oxide cycloalkyl group, alkylene oxide heterocyclic group, alkylene oxide heterocyclic alkyl, alkylene oxide alkenyl group, alkylene oxide cycloalkenyl group, alkylene oxide aromatic group, alkylene oxide heteroaromatic group, cycloalkylene oxide alkyl group, cycloalkylene oxide cycloalkyl group, cycloalkylene oxide heterocyclic group, cycloalkylene oxide heterocyclic alkyl, cycloalkylene oxide alkenyl group, cycloalkylene oxide cycloalkenyl group, cycloalkylene oxide aromatic group, cycloalkylene oxide heteroaromatic group, cycloalkylene oxide alkyl group, cycloalkylene oxide cycloalkyl group, cycloalkylene oxide heterocyclic group, cycloalkylene oxide heterocyclic alkyl, cycloalkylene oxide alkenyl group, cycloalkylene oxide cycloalkenyl group, cycloalkylene oxide One of the group consisting of aromatic group, cycloalkylene oxide heteroaromatic group, heterocycloalkylene oxide alkyl group, heterocycloalkylene oxide cycloalkyl group, heterocycloalkylene oxide heterocyclic group, heterocycloalkylene oxide heterocyclic group, heterocycloalkylene oxide heterocyclic group, heterocycloalkylene oxide alkenyl group, heterocycloalkylene oxide cycloalkenyl group, heterocycloalkylene oxide aromatic group, heterocycloalkylene oxide heteroaromatic group, aromatic oxide alkyl group, aromatic oxide cycloalkyl group, aromatic oxide heterocyclic group, aromatic oxide heterocyclic group, aromatic oxide alkenyl group, aromatic oxide cycloalkenyl group, aromatic oxide aromatic group and aromatic oxide heteroaromatic group.
[0006] Further, in the structural formula, R2, R3, R4, R5, R6, and R7 are each independently selected from the group consisting of alkylene, alkylene heteroalkylene, alkenylene, alkene heteroalkenylene, alkylene heteroalkenylene, alkynylene, cycloalkylene, alkylene cycloalkylene, alkylene cycloalkylene alkylene, alkene cycloalkylene, alkene cycloalkylene alkenylene, alkylene cycloalkylene alkenylene, alkynylene cycloalkylene, alkynylene cycloalkylene alkynylene, heterocycloalkylene, alkylene heterocycloalkylene, alkylene heterocycloalkylene, alkene heterocycloalkylene, alkene heterocycloalkylene alkenylene, alkynylene heterocycloalkylene, alkynylene heterocycloalkylene, cycloalkylene, alkylene cycloalkylene, alkylene cycloalkylene, alkynyl ... The invention relates to an alkenylene group, an alkylene cycloalkenylene group, an alkynyl ...
[0007] Furthermore, in the structural formula, R2, R3, R4, R5, R6, and R7 may be the same.
[0008] Furthermore, in the structural formula, R2, R3, R4, R5, R6, and R7 may be different.
[0009] As a preferred embodiment of the degradable and recyclable low-loss white copper-clad laminate resin composition of the present invention, in the structural formula of the degradable curing agent, R1 includes an aromatic group; R2 includes an aromatic olefin; R3 includes an aromatic olefin; R4 includes an aromatic olefin; R5 includes an aromatic olefin; R6 includes an aromatic olefin; and R7 includes an aromatic olefin.
[0010] Furthermore, the degradable curing agent includes a degradable curing agent having the following molecular structure: .
[0011] Furthermore, the following components are also included: alicyclic epoxy resin, polyphenylene ether resin, hydrocarbon resin, filler, fluorescent brightener, solvent, and initiator.
[0012] Furthermore, the invention comprises the following components in parts by mass: 10 to 20 parts of the degradable curing agent, 10 to 20 parts of the alicyclic epoxy resin, 20 to 35 parts of the hydrocarbon resin, 50 to 70 parts of the polyphenylene ether resin, 50 to 100 parts of the solvent, 10 to 100 parts of the filler, 0.1 to 10 parts of the fluorescent whitening agent, and 0.01 to 5 parts of the initiator.
[0013] Furthermore, the alicyclic epoxy resin includes one or more of alicyclic glycidyl ether and alicyclic glycidyl ester; the polyphenylene ether resin includes one or more of acrylate-terminated polyphenylene ether, methacrylate-terminated polyphenylene ether and styrene-terminated polyphenylene ether; the hydrocarbon resin includes one or more of polybutadiene, polystyrene, polystyrene-butadiene, polyisobutadiene and polystyrene-isobutadiene.
[0014] Furthermore, in the above-mentioned degradable and recyclable low-loss white copper-clad laminate resin composition, the filler includes one or more of spherical silica, titanium dioxide, silicon micropowder, aluminum oxide, boron nitride and barium titanate; The fluorescent whitening agent includes one or more of stilbene derivatives, phenylpyrazoline derivatives, benzimidazole derivatives, phenylpyrazole derivatives, coumarin derivatives or naphthalimide derivatives; The solvent includes one or more of acetone, butanone, cyclohexanone, methyl isobutyl ketone, toluene, xylene, propylene glycol monomethyl ether, propylene glycol methyl ether acetate, N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide.
[0015] The initiator includes one or more of benzoyl peroxide, di-tert-butyl peroxide, dicumyl peroxide, di-tert-butyl peroxide isopropylbenzene and tert-butyl perbenzoate.
[0016] Furthermore, the above-mentioned degradable and recyclable low-loss white copper-clad laminate resin composition is a glue liquid, and the solid content of the glue liquid is 45-80%.
[0017] Accordingly, the present invention also provides a method for preparing the above-mentioned degradable and recyclable low-loss white copper-clad laminate resin composition: A, adding the solvent to the degradable curing agent, and mixing them evenly to obtain a mixture m; B. Adding the hydrocarbon resin, the alicyclic epoxy resin, the polyphenylene ether resin, the filler and the fluorescent brightener into the mixture m, and mixing them evenly to obtain a mixture n; C. Add the initiator into the mixture n, mix them evenly to obtain the degradable and recyclable low-loss resin composition for white copper-clad laminates.
[0018] Furthermore, in step A, step B and step C, the uniform mixing method includes stirring.
[0019] Furthermore, in the preparation method of the biodegradable and recyclable low-loss white copper-clad laminate resin composition: the stirring speed in step A includes 1500 rpm, and the stirring time includes 60 to 120 minutes; the stirring speed in step B includes 1800 rpm, and the stirring time includes 60 minutes; the stirring speed in step C includes 1800 rpm, and the stirring time includes 30 minutes.
[0020] Correspondingly, the present invention also provides an application of the above-mentioned degradable and recyclable low-loss white copper clad laminate resin composition, wherein the degradable and recyclable low-loss white copper clad laminate resin composition is used to prepare one or more of a prepreg and a copper clad laminate.
[0021] Furthermore, the prepreg is prepared by the following method: impregnating a reinforcing material into the degradable and recyclable low-loss white copper-clad laminate resin composition, and obtaining the prepreg after drying; the drying method includes heating.
[0022] Furthermore, the copper clad laminate comprises copper foil and the above-mentioned prepreg; the copper foil is arranged on at least one side surface of the prepreg; and the number of the prepregs includes one or more.
[0023] Furthermore, the copper clad laminate is made by the following method: cutting the prepreg, covering both sides with copper foil, laminating them, and placing them in a press for hot pressing and curing.
[0024] Furthermore, in the method for preparing the prepreg, the heating temperature is 140 to 200° C. and the heating time is 2 to 3 minutes.
[0025] Furthermore, in the above-mentioned method for preparing the copper clad laminate, the pressure of the hot pressing curing includes 2 to 6 MPa, the temperature of the hot pressing curing includes 150 to 200° C., and the time of the hot pressing curing includes 60 to 140 min.
[0026] Correspondingly, the present invention also provides a product obtained according to the above application, wherein the product includes one or more of a prepreg and a copper clad laminate.
[0027] Accordingly, the present invention also provides a recycling method according to the above product, comprising the following steps: S1, soaking the product in an acidic solvent, heating and ultrasonically shaking at the same time, filtering to obtain a solid mixture a; S2, washing the solid mixture a with an alkaline solvent, filtering, and obtaining a solid mixture b; S3, soaking the solid mixture b in a decomposing agent, heating and ultrasonically vibrating at the same time, filtering to obtain a residual solid; S4, washing and drying the remaining solid to obtain recycled glass fiber; The decomposition agent includes one or more of a mercaptoethanol aqueous solution, a mercaptopropanol aqueous solution, a mercaptobutanol aqueous solution, and a mercaptopentanol aqueous solution; in step S1, the heating temperature includes 60 to 100° C.; in step S3, the heating temperature includes 60 to 100° C.; when the product is a copper clad laminate, the copper foil is peeled off from the surface of the product before step S1.
[0028] Furthermore, the concentration of the decomposing agent ranges from 10wt% to 90wt%.
[0029] Furthermore, the preparation method of the degradable curing agent comprises the following steps: Step 1: adding methyltetrahydrofuran, hydroxybenzaldehyde, triethylamine and dichlorophenylphosphine, stirring and refluxing for reaction, filtering and pouring into ice water to obtain crystals, and drying the crystals to obtain bis(4-formylphenyl)phenylphosphonate; Step 2: dissolving the bis(4-formylphenyl)phenylphosphonate obtained in step 1 in ethyl acetate to obtain solution 1, dissolving 4,4'-dithiodiphenylamine in ethanol solution to obtain solution 2, mixing solution 1 and solution 2, freezing under a nitrogen atmosphere, distilling and washing with ether to obtain the degradable curing agent.
[0030] Furthermore, in the above-mentioned method for preparing the prepreg, the heating method includes baking; the heating temperature includes 150 to 200° C., and the heating time includes 200 to 800 seconds.
[0031] Furthermore, in the above recovery method: In step S1, the acidic solvent includes one or more of formic acid solution, acetic acid solution, propionic acid solution, sulfuric acid solution, hydrofluoric acid solution, trichloroacetic acid solution, hydrochloric acid solution, and boric acid solution; In step S2, the alkaline solvent includes one or more of sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution or ammonia solution.
[0032] Furthermore, in the above-mentioned recycling method: in step S1, ultrasonic oscillation is performed until the plate swells; in step S2, cleaning is performed until the pH value is neutral; in step S3, the concentration of the decomposition agent includes 10 to 90 wt%; in step S3, the heating and the ultrasonic oscillation are both terminated when the resin layer is completely dissolved; in step S4, the cleaning includes cleaning with distilled water.
[0033] Furthermore, in the above recovery method, the filtration in step S1, step S2, and step S3 all uses a 400-mesh filter.
[0034] The invention has explored the preparation of a degradable curing agent with a molecular structure such as a structural formula after a large number of experiments, thereby preparing a degradable curing agent with better degradation efficiency, yield, etc., effectively solving the problem of difficult degradation of white copper clad laminates, and effectively solving the problem of large dielectric loss. The invention has the advantages of meeting various LED performance indicators, excellent dielectric properties, easy recycling, mild and rapid degradation conditions, and reusable degradation and recycling products. The invention can be applied to the field of manufacturing degradable and recyclable LED white copper clad laminates and the field of high-frequency and high-speed copper clad laminates.
[0035] Compared with the prior art, the present invention has the following beneficial effects: 1. The self-made degradable curing agent of the present invention contains chemical bonds that are easily hydrolyzed, such as disulfide bonds and Schiff base bonds, and the degradable curing agent also contains elements with flame retardant effects.
[0036] 2. Compared with white copper clad laminates prepared with other degradable curing agents, the white copper clad laminates prepared with the degradable curing agent of the present invention have two advantages: 1) the degradation time is shortened by at least half, and 2) the flame retardant performance is significantly enhanced.
[0037] 3. The degradable curing agent of the present invention is combined with alicyclic epoxy resin, polyphenylene ether resin, hydrocarbon resin, etc. to prepare a degradable and recyclable resin composition for low-loss white copper-clad laminates, and the resin composition is used to prepare prepregs and white copper-clad laminates, solving the technical problem of difficult degradation of low-loss prepregs and white copper-clad laminates.
[0038] 4. Compared with traditional white LED copper-clad laminates, the copper-clad laminates prepared with the degradable and recyclable low-loss white copper-clad laminate resin composition of the present invention have better degradation efficiency and higher recovery rate. Under this premise, the flame retardant grade of the comparative example V2 is improved to V0 of the embodiment.
[0039] 5. The recycling method of the white copper clad laminate of the present invention has the advantages of recyclable materials being reusable and having a high recycling rate. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below in conjunction with specific implementation methods.
[0041] Preparation example of degradable curing agent Step 1: Take a three-necked round-bottom glass flask, first add 400 ml of methyltetrahydrofuran and then add 0.6 mol of hydroxybenzaldehyde, 0.5 mol of triethylamine and 0.2 mol of dichlorophenylphosphine, stir and reflux for 10 hours, filter and pour into ice water to obtain a white crystalline solid, and then dry to obtain bis(4-formylphenyl)phenylphosphonate.
[0042] Step 2: The bis(4-formylphenyl)phenylphosphonate obtained in step 1 was dissolved in 200 mL of ethyl acetate. 0.21 mol of 4,4'-dithiodiphenylamine (0.21 mol, 52.16 g) was first completely dissolved in 550 ml of ethanol solution, added and incubated at -10 °C for 4 hours under a nitrogen atmosphere. After distillation, it was washed with ether to obtain a dark yellow powder of bis(4-(((4-((4-benzaldehyde)disulfide)phenyl)imino)methyl)phenyl)phenylphosphonate, i.e., curing agent D1, with the molecular structure as shown below.
[0043]
[0044] Preparation Example of Resin Composition According to each embodiment or comparative example as a group, each component of each group was weighed according to the component dosage in Table 1; at room temperature, 100 parts by mass of butanone was taken as a solvent in each group, the rotation speed was maintained at 1500 rpm, and the degradable curing agent was added and stirred for 60 minutes; hydrocarbon resin, alicyclic epoxy resin, polyphenylene ether resin, filler and fluorescent brightener were slowly added, and stirred at a rotation speed of 1800 rpm for 60 minutes; an initiator was added, and stirring was continued for 30 minutes to dissolve and mix the components evenly, so as to obtain a glue solution (i.e., a resin composition) with a solid content of about 66%.
[0045] Table 1 Amount of each component of the resin composition (in parts by mass)
[0046] In Table 1, the information of each component is as follows: Alicyclic epoxy resin A1: (CE2021, Chengdu Keyi Polymer Technology Co., Ltd.); Alicyclic epoxy resin A2: (TTA3150, Jiangsu Taitel Co., Ltd.); Polyphenylene ether resin B1: (SA9000, Saudi Basic Industries Corporation); Polyphenylene ether resin B2: (OPE-2st 2200, Mitsubishi Gas Chemical Co., Ltd., Japan); Hydrocarbon resin C1: butadiene homopolymer (Ricon130, Créville, France); Hydrocarbon resin C2: styrene-butadiene copolymer (Ricon100, Créville, France); Degradable curing agent D1: di(4-(((4-((4-benzaldehyde)disulfide)phenyl)imino)methyl)phenyl)phenylphosphonate; D1 is prepared by the method of the preparation example of the degradable curing agent of the present invention; Degradable curing agent D2: degradable isocyanate (Cleavamine, Aidaso High-tech Materials Co., Ltd.); Degradable curing agent D3: degradable amine curing agent (ACP-2004, Aidaso High-tech Materials Co., Ltd.); Degradable curing agent D4: 4,4'-diphenyldisulfide, Aladdin Scientific Reagent Co., Ltd.; Degradable curing agent D5: Degradable imine curing agent (KT-22, Evonik Industries AG), curing agent D5 contains Schiff base bonds; Filler E1: titanium dioxide (TDE, Suzhou Jinyi New Materials Technology Co., Ltd.); Filler E2: spherical silica (Q103, Suzhou Jinyi New Materials Technology Co., Ltd.); Fluorescent brightener: (OB-1, Shanghai Aladdin Biochemical Technology Co., Ltd.); Initiator: Benzoyl peroxide (BPO, Hubei Xinghengye Co., Ltd.).
[0047] Prepreg Preparation Example Each example or comparative example in Table 1 is a group. The resin composition prepared in the preparation example of the resin composition is impregnated into 2116 glass cloth, and then baked in an oven at 171° C. for 2 to 3 minutes to obtain prepregs of each group.
[0048] Copper Clad Laminate Preparation Example According to Table 1, each embodiment or comparative example is a group, and 6 prepregs prepared in the above prepreg preparation example are taken in each group, stacked in groups, covered with copper foil (1Oz HTE copper foil) on both sides, pressed in a hot press at 2-6Mpa and 170°C for 60min, and cooled naturally to obtain copper clad laminates with a thickness of about 1.0mm in each group.
[0049] Effect Example 1 Each group of copper clad laminates prepared in the copper clad laminate preparation example (Examples 1, 2, 3 and Comparative Examples 1, 2, 3, 4, 5) were taken for performance testing. The performance testing method of the copper clad laminate is as follows: (1) Glass transition temperature (Tg): tested using the DMA method in accordance with IPC-TM-650 2.4.24.2.
[0050] (2) Dielectric properties (Dk / Df): Tested according to IPC-TM-650 2.5.5.9 method, frequency is 3 GHz.
[0051] (3) Flame retardancy: tested using IPC-TM-650 2.3.10 method.
[0052] (4) Water absorption rate: The sample with copper foil removed from both sides was cooked in a pressure cooker at 121°C and 105 kPa for 1 hour. The water absorption rate was calculated based on the weight before and after cooking.
[0053] Effect Example 2 Take each group of copper clad laminates prepared in the copper clad laminate preparation example (Examples 1, 2, 3 and Comparative Examples 1, 2, 3, 4, 5), first peel off the copper foil on the surface of the copper clad laminate samples, and then degrade and recycle the prepared copper clad laminates according to the following steps, and measure their respective degradation times and glass fiber recovery rates.
[0054] Step 1: Soak in hydrochloric acid at 80°C for 1 hour, and ultrasonically vibrate until the plate swells, and filter with a 400-mesh filter; Step 2: Wash with sodium hydroxide aqueous solution until the pH value is neutral, and filter with a 400-mesh filter; Step 3: soak with 2-mercaptoethanol solvent, heat at 80°C for 4 hours and ultrasonically vibrate until the resin layer is completely dissolved, and filter with a 400-mesh filter to obtain the remaining solid; Step 4: The remaining solid is washed with distilled water and dried to obtain the recovered glass fiber.
[0055] Method for determining the recovery rate of glass fiber: weigh the total weight W of the recovered glass fiber 2 , and the weight of the glass fiber sample before recycling W 1 The ratio of (unit %).
[0056] Determination method of degradation time: the start time of complete dissolution of the sample is taken as the beginning of the above-mentioned recovery step 1, and the end time of complete dissolution of the sample is taken as the complete dissolution of the resin layer in the above-mentioned recovery step 3. The difference between the latter and the former is the time taken for the sample to be completely dissolved, recorded as the degradation time (unit: h).
[0057] The results of various tests on the copper clad laminates prepared in Examples 1 to 3 and Comparative Examples 1 to 5 in Effect Example 1 and Effect Example 2 are shown in Table 2.
[0058] Table 2 Performance test and recovery test results of each group of copper clad laminates
[0059] It can be seen from the main performance data of the copper clad laminate in Table 2 that the various properties of the copper clad laminates of Example 1, Example 2, and Example 3 meet the requirements of IPC4101 / 126 and meet the requirements for the use of ordinary FR-4 copper clad laminates.
[0060] The data analysis of Table 2 is as follows: Compared with Examples 1 to 3, the resin composition of Comparative Example 1 shows that after the degradable curing agent (D1) of the present invention in the example is replaced with the degradable cyanate curing agent (D2) of Comparative Example 1, the degradation time of the board is significantly prolonged and the flame retardancy is deteriorated. Moreover, the resin composition of Examples 1 to 3 does not need to use isocyanate, so its water absorption rate is also significantly better than that of Comparative Example 1.
[0061] Compared with Examples 1 to 3, the resin composition of Comparative Example 2 has poor flame retardancy when the curing agent (D1) of the present invention in the examples is replaced with the degradable amine curing agent (D3) of Comparative Example 2.
[0062] The resin composition of Comparative Example 3 uses both the degradable cyanate ester (D2) of Comparative Example 1 and the degradable amine curing agent (D3) of Comparative Example 2. The flame retardancy and degradability of the board are not good, and are basically equivalent to those of Comparative Example 1.
[0063] The resin composition of comparative example 4 uses 4,4'-dithiodiphenylamine as a curing agent (D4), the resin composition of comparative example 5 uses a degradable imine curing agent as a curing agent (D5), and the resin compositions of examples 1 to 3 use the self-made degradable curing agent (D1) of the present invention. From the data in Table 2, it can be seen that the degradation time of the plates of the examples is shortened by more than half compared with comparative example 4 or comparative example 5, and the degradation time of the plates of comparative example 4 is shortened by about 60%; and for the glass fiber recovery rate, the examples are increased by 24% to 26% compared with comparative example 4, and by 21% to 23% compared with comparative example 5. The main reason is that multiple easily hydrolyzed bonds (disulfide bonds, Schiff base bonds) work together to achieve a synergistic degradation effect of 1+1>2.
[0064] In addition, the flame retardancy of the panels of Examples 1 to 3 all reached V0 level, which was significantly improved compared with the V2 level of the panels of Comparative Examples 1 to 5. It is speculated that this is related to the fact that the degradable curing agent used in the resin composition in the embodiments of the present invention contains phosphorus.
[0065] In summary, in the recycling test results of Examples 1 to 3, the degradation time and glass fiber recovery rate are significantly better than those of Comparative Examples 1 to 5, wherein the degradation time is shortened by half or more; in the performance test results of Examples 1 to 3, the flame retardancy is significantly better than that of Comparative Examples 1 to 5. Therefore, the use of the degradable curing agent of the present invention and the preparation method of the present invention to prepare the resin composition, prepreg and white copper clad laminate, compared with the degradable curing agent in the prior art used to prepare the white copper clad laminate, has achieved technical progress such as better flame retardancy of the board, shorter degradation time and higher recovery rate.
[0066] The above disclosure is only the preferred embodiment of the present invention, which cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.
Claims
1. A degradable and recyclable low-loss white copper-clad laminate resin composition, characterized in that: Including a degradable curing agent; the degradable curing agent includes one or more degradable curing agents having the following structural formula: Wherein, R1 includes hydrogen atom, alkyl, cycloalkyl, heterocyclic group, heterocyclic alkyl, alkenyl, cycloalkenyl, alkynyl, aromatic group, heteroaromatic group, alkylene oxide group, alkylene oxide cycloalkyl group, alkylene oxide heterocyclic group, alkylene oxide heterocyclic alkyl, alkylene oxide alkenyl group, alkylene oxide cycloalkenyl group, alkylene oxide aromatic group, alkylene oxide heteroaromatic group, cycloalkylene oxide alkyl group, cycloalkylene oxide cycloalkyl group, cycloalkylene oxide heterocyclic group, cycloalkylene oxide heterocyclic alkyl, cycloalkylene oxide alkenyl group, cycloalkylene oxide cycloalkenyl group, cycloalkylene oxide aromatic group, cycloalkylene oxide heteroaromatic group, cycloalkylene oxide alkyl group, cycloalkylene oxide cycloalkyl group, cycloalkylene oxide heterocyclic group, cycloalkylene oxide heterocyclic alkyl, cycloalkylene oxide alkenyl group, cycloalkylene oxide cycloalkenyl group, cycloalkylene oxide One of the group consisting of aromatic group, cycloalkylene oxide heteroaromatic group, heterocycloalkylene oxide alkyl group, heterocycloalkylene oxide cycloalkyl group, heterocycloalkylene oxide heterocyclic group, heterocycloalkylene oxide heterocyclic group, heterocycloalkylene oxide heterocyclic group, heterocycloalkylene oxide alkenyl group, heterocycloalkylene oxide cycloalkenyl group, heterocycloalkylene oxide aromatic group, heterocycloalkylene oxide heteroaromatic group, aromatic oxide alkyl group, aromatic oxide cycloalkyl group, aromatic oxide heterocyclic group, aromatic oxide heterocyclic group, aromatic oxide alkenyl group, aromatic oxide cycloalkenyl group, aromatic oxide aromatic group and aromatic oxide heteroaromatic group.
2. The degradable and recyclable low-loss white copper-clad laminate resin composition according to claim 1, characterized in that: In the structural formula, R2, R3, R4, R5, R6, and R7 are each independently selected from the group consisting of alkylene, alkylene heteroalkylene, alkenylene, alkene heteroalkenylene, alkylene heteroalkenylene, alkynylene, cycloalkylene, alkylene cycloalkylene, alkylene cycloalkylene alkylene, alkene cycloalkylene, alkene cycloalkylene alkenylene, alkylene cycloalkylene alkenylene, alkynylene cycloalkylene, alkynylene cycloalkylene alkynylene, heterocycloalkylene, alkylene heterocycloalkylene, alkylene heterocycloalkylene, alkene heterocycloalkylene, alkene heterocycloalkylene alkenylene, alkynylene heterocycloalkylene, alkynylene heterocycloalkylene, cycloalkylene, alkylene cycloalkylene, alkylene cycloalkylene, alkynyl ... The invention relates to an alkenyl group, an alkylenecycloalkenylene alkenylene group, an alkynylenecycloalkenylene group, an alkynylenecycloalkenylene group alkynylene group, a heterocycloalkenylene group, an alkyleneheterocycloalkenylene group, an alkyleneheterocycloalkenylene group, an alkyleneheterocycloalkenylene group, an alkyleneheterocycloalkenylene group, an alkynyl ...
3. The degradable and recyclable low-loss white copper-clad laminate resin composition according to claim 1, characterized in that: The degradable curing agent includes a degradable curing agent having the following molecular structure: 。 4. The degradable and recyclable low-loss white copper-clad laminate resin composition according to claim 1, characterized in that: The invention also comprises the following components: alicyclic epoxy resin, polyphenylene ether resin, hydrocarbon resin, filler, fluorescent brightener, solvent and initiator.
5. The degradable and recyclable low-loss white copper-clad laminate resin composition according to claim 4, characterized in that: The invention comprises the following components in parts by mass: 10 to 20 parts of the degradable curing agent, 10 to 20 parts of the alicyclic epoxy resin, 20 to 35 parts of the hydrocarbon resin, 50 to 70 parts of the polyphenylene ether resin, 50 to 100 parts of the solvent, 10 to 100 parts of the filler, 0.1 to 10 parts of the fluorescent whitening agent and 0.01 to 5 parts of the initiator.
6. The degradable and recyclable low-loss white copper-clad laminate resin composition according to claim 4, characterized in that: The alicyclic epoxy resin includes one or more of alicyclic glycidyl ether and alicyclic glycidyl ester; the polyphenylene ether resin includes one or more of acrylate-terminated polyphenylene ether, methacrylate-terminated polyphenylene ether and styrene-terminated polyphenylene ether; the hydrocarbon resin includes one or more of polybutadiene, polystyrene, polystyrene-butadiene, polyisobutadiene and polystyrene-isobutadiene.
7. A method for preparing the degradable and recyclable low-loss white copper-clad laminate resin composition according to claim 4, characterized in that: The following steps are involved: A, adding the solvent to the degradable curing agent, and mixing them evenly to obtain a mixture m; B. Adding the hydrocarbon resin, the alicyclic epoxy resin, the polyphenylene ether resin, the filler and the fluorescent brightener into the mixture m, and mixing them evenly to obtain a mixture n; C. Add the initiator into the mixture n, mix them evenly to obtain the degradable and recyclable low-loss resin composition for white copper-clad laminates.
8. An application of the degradable and recyclable low-loss white copper-clad laminate resin composition according to any one of claims 1 to 6, characterized in that: The degradable and recyclable low-loss white copper-clad laminate resin composition is used to prepare one or more of a prepreg and a copper-clad laminate.
9. A product obtained by the application according to claim 8, characterized in that: The product includes one or more of a prepreg and a copper clad laminate.
10. A method for recycling the product according to claim 9, characterized in that: The steps include: S1, soaking the product in an acidic solvent, heating and ultrasonically shaking at the same time, filtering to obtain a solid mixture a; S2, washing the solid mixture a with an alkaline solvent, filtering, and obtaining a solid mixture b; S3, soaking the solid mixture b in a decomposing agent, heating and ultrasonically vibrating at the same time, filtering to obtain a residual solid; S4, washing and drying the remaining solid to obtain recycled glass fiber; The decomposition agent includes one or more of a mercaptoethanol aqueous solution, a mercaptopropanol aqueous solution, a mercaptobutanol aqueous solution, and a mercaptopentanol aqueous solution; in step S1, the heating temperature includes 60 to 100° C.; in step S3, the heating temperature includes 60 to 100° C.; when the product is a copper clad laminate, the copper foil is peeled off from the surface of the product before step S1.
Citation Information
Patent Citations
Degradable resin compound, prepreg prepared from same, laminated board and recovery method thereof
CN106750182A
Degradable imine type epoxy resin curing agent as well as preparation method and application thereof
CN110218294A
Recyclable epoxy wind turbine blade material and preparation method and recycling method thereof
CN115594949A
Resin composition
CN118684998A